France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper examines the causes and potential remedies for structural unemployment in France. Structural unemployment in France has long been elevated, and appears to have edged up further since the crisis. This reflects both demand and supply factors, including: high labor taxes, wage stickiness, a growing skill gap, hysteresis effects from the crisis years, a lengthy period of elevated economic uncertainty, inactivity traps created by the unemployment and welfare benefit systems, and demographic factors that have pushed up the labor force. The cyclical recovery is projected to bring down the unemployment rate only slowly. Reducing labor tax wedges can increase both output and employment.